A reply to Mueller (2018) Supply chain collaboration: Further insights into incentive alignment in the Beer Game scenario - Borja Ponte; Isabel Fernández; Rafael Rosillo; José Parreño; Nazario García (Journal of Industrial Engineering and Management, 2018)
Purpose: We expand a previous discussion in this journal by proposing a new solution concept, based on game theory, for profit allocation with the aim of aligning incentives in collaborative supply chains.